Improvement of mercuric chloride-induced testis injuries and sperm quality deteriorations by Spirulina platensis in rats. - Gaber E El-Desoky; Samir A Bashandy; Ibrahim M Alhazza; Zeid A Al-Othman; Mourad A M Aboul-Soud; Kareem Yusuf (PLoS ONE, 2013)
The present study was undertaken to investigate the protective effect of the filamentous cyanobacterium Spirulina platensis (S. platensis) on mercury (II) chloride (HgCl(2))-induced oxidative damages and histopathological alterations in the testis of Wistar albino rats. The animals were divided into four equal groups, i) control, ii) HgCl(2), iii) S. platensis and iv) combination of HgCl(2)+S. platensis. Oxidative stress, induced by a single dose of HgCl(2) (5 mg/kg, bw; subcutaneously, s.c.), substantially decreased (P<0.01) the activity level of testicular key enzymatic antioxidant biomarkers (superoxide dismutase, SOD; catalase, CAT and glutathione peroxidase, GPx), oxidative stress makers (blood hydroperoxide; testicular reduced glutathione, GSH and malondialdehyde, MDA), and testicular mercury levels. Moreover, HgCl(2) administration resulted in a significant (P<0.01) increase in the number of sperms with abnormal morphology and decrease in epididymal sperm count, motility, plasma testosterone level and testicular cholesterol. Furthermore, HgCl(2) exposure induced histopathological changes to the testis including morphological alterations of the seminiferous tubules, and degeneration and dissociation of spermatogenic cells. Notably, oral pretreatment of animals with Spirulina (300 mg/kg, bw) lowered the extent of the observed HgCl(2)-mediated toxicity, whereby significantly reducing the resulting lipid peroxidation products, mercury accumulation in the testis, histopathological changes of the testes and spermatozoal abnormalities. In parallel, the pretreatment with Spirulina also completely reverted the observed Hg-Cl(2)-induced inhibition in enzymatic activities of antioxidant biomarkers (SOD, CAT and GPx) back to control levels. The pretreatment of rats with S. platensis significantly recovered the observed HgCl(2)-mediated decrease in the weight of accessory sex organs. Taken together, our findings clearly highlight the role of S. platensis as a protective modulator of HgCl(2)-induced testicular injuries and suggest some therapeutic potential in mammals. Further investigation of therapeutic strategies employing Spirulina against heavy metals toxicity in humans is therefore warranted.